MicroRNA-20a Suppresses Tumor Proliferation and Metastasis in Hepatocellular Carcinoma by Directly Targeting EZH1 - Zhang, Qianqian; Deng, Xiaohong; Tang, Xiuxin; You, Ying; Mei, Meihua; Liu, Danping; Gui, Lian; Cai, Yan; Xin, Xiaoping; He, Xiaoshun; Huang, Junqi (Frontiers in Oncology, 2021)
Purpose Hepatocellular carcinoma (HCC), a worldwide leading cause of morbidity and mortality, is the most frequent primary liver tumor. Most HCC patients are diagnosed with advanced liver cancer, resulting in a very low 5-year survival rate. Thus, there is an urgent need for the development of targeted therapies. In this study, we aimed to investigate the effect and mechanism of the miR-20a/EZH1 axis on the proliferation and metastasis of HCC and the inhibitory effect of the EZH1/EZH2 inhibitor UNC1999 on HCC. Materials and Methods The expression of miR-20a in human HCC tissues and cell lines was detected using quantitative real-time PCR (qRT-PCR). The expressions of proteins were analyzed with immunohistochemistry and Western blotting. Luciferase assay was used to verify whether miR-20a targets EZH1 or EZH2. The effect of miR-20a on HCC progression was studied in vivo and in vitro. The tumor inhibitory effect of UNC1999 was confirmed in vivo. CCK8 assay, wound healing assay, cell migration and invasion assay were used to evaluate the synergistic effect of UNC1999 with sorafenib. RNA sequencing (RNA-seq) was performed to screen the differentially expressed genes in the Huh7 and SMMC7721 cell lines after UNC1999, sorafenib, and combination treatments. Results In this study, miR-20a showed a lower expression in both HCC tissues and cell lines. MiR-20a inhibited the proliferation and migration of SMMC7721 and Huh7 cells. The results of the luciferase assay and Western blot analysis revealed that miR-20a directly targeted EZH1, a histone methyltransferase. We demonstrated that miR-20a negatively regulated the expression of EZH1 and inhibited the proliferation and metastasis of HCC by reducing H3K27 methylation. We found UNC1999 inhibited tumor cells proliferation and enhanced the inhibitory effect of sorafenib. Conclusion We demonstrated that miR-20a suppresses the tumor proliferation and metastasis in HCC by directly targeting EZH1. UNC1999 can inhibit tumor proliferation in vivo and increase the sensitivity of hepatoma cell lines to sorafenib.